Effect of anti‐interleukin‐17 biologics on Krebs von den Lungen‐6 level in patients with psoriasis. Issue 6 (16th April 2021) - Hara, Hiromichi; Miyagawa, Hanae; Araya, Jun; Minagawa, Shunsuke; Numata, Takanori; Umezawa, Yoshinori; Asahina, Akihiko; Nakagawa, Hidemi; Kuwano, Kazuyoshi
Abstract: Interleukin (IL)‐17 plays critical roles in the pathogenesis of both psoriasis and interstitial pneumonia (IP). We hypothesized that anti‐IL‐17 biologics might suppress both clinically relevant and latent IP activity and decrease Krebs von den Lungen‐6 (KL‐6) level in psoriasis patients. We aimed to elucidate the effects of anti‐IL‐17 biologics on KL‐6 levels. We retrospectively analyzed the clinical data of psoriasis patients treated with anti‐IL‐17 biologics. KL‐6 levels were measured before treatment (baseline) and at 3 and 6 months after the initiation of the treatment, and ratios of KL‐6 levels at each time point to the baseline levels were calculated. Chest computed tomography (CT) was performed on patients with coexisting IP. The clinical characteristics and radiographic findings were evaluated. A total of 294 psoriasis patients were treated with anti‐IL‐17 biologics. Baseline KL‐6 levels were higher than 401 U/mL in 34 patients (high baseline KL‐6 group). While anti‐IL‐17 biologics did not affect KL‐6 levels and ratios of KL‐6 to the baseline levels at any time point in the overall study population, they decreased both KL‐6 levels and ratios at 6 months after the initiation of the treatment in the high baseline KL‐6 group. A total of 10 patients with coexisting IP showed decreasing ratios of KL‐6 to the baseline levels at 6 months without affecting coexisting IP in CT performed at 3–12 months. Anti‐IL‐17 biologics decreased KL‐6 levels in the high baseline KL‐6 group regardless of recognizable IP. A decrease in KL‐6 levels was not associated with a radiographic improvement of IP, which should be examined in large numbers with long‐term observations in future studies.